An observational study to assess awareness of cervical cancer among the adult women of field practice area of urban health training center in Kolkata - Sonali Sain; Dey, Indira; Chakraborty, Nabanita (Asian Journal of Medical Sciences, 2024)
Background: Cervical cancer is a major public health problem, especially worldwide. Lack of awareness about the risk factors, signs and symptoms, and danger signs has led to a rise in the prevalence of the disease in countries like India. Aims and Objectives: The aim of the study was to assess the awareness of cervical cancer and its risk factors among the adult female population residing in the urban slum of Kolkata Municipal Corporation area and their attitude toward the disease. Materials and Methods: A cross-sectional study was conducted among 720 adult female residents of the field practice area of the urban health training center of NRS Medical College using a predesigned pretested questionnaire. Results: In the current study, 58.3% of subjects were married at <18 years of age and 38.3% with >2 children. A significant association was found among inter-menstrual bleeding and persistent low back pain with a family history of cancer, persistent vaginal discharge, and postmenopausal bleeding with education, dyspareunia showed significant association with age, education, and family type, heavy menstruation with religion. Furthermore, the association between postcoital bleeding with education and blood in the urine or stool with marital status was found to be significant. A significant association was found between confidences about noticing a symptom with marital status (P<0.05). Conclusion: Unsatisfactory knowledge about cervical cancer among adult women in an urban slum poses the risk of the disease. Awareness of risk factors of cervical cancer, along with early diagnosis and treatment, can decline the burden of the disease.